Chronic Trypanosoma cruzi-elicited cardiomyopathy: from the discovery to the proposal of rational therapeutic interventions targeting cell adhesion molecules and chemokine receptors - how to make a dream come true - Joseli Lannes-Vieira; Jaline Coutinho Silverio; Isabela Resende Pereira; Nathália Ferreira Vinagre; Cristiano Marcelo Espinola Carvalho; Cláudia Neto Paiva; Andréa Alice da Silva (Memorias do Instituto Oswaldo Cruz, 2009)
One hundred years ago, Carlos Chagas discovered a new disease, the American trypanosomiasis. Chagas and co-workers later characterised the disease's common manifestation, chronic cardiomyopathy, and suggested that parasitic persistence coupled with inflammation was the key underlying pathogenic mechanism. Better comprehension of the molecular mechanisms leading to clinical heart afflictions is a prerequisite to developing new therapies that ameliorate inflammation and improve heart function without hampering parasite control. Here, we review recent data showing that distinct cell adhesion molecules, chemokines and chemokine receptors participate in anti-parasite immunity and/or detrimental leukocyte trafficking to the heart. Moreover, we offer evidence that CC-chemokine receptors may be attractive therapeutic targets aiming to regain homeostatic balance in parasite/host interaction thereby improving prognosis, supporting that it is becoming a non-phantasious proposal.